Clinical role of swept source optical coherence tomography in anterior segment diseases: a review. (17th November 2021) - Pujari, Amar; Agarwal, Divya; Sharma, Namrata
ABSTRACT: Purpose: To note the comprehensive role of swept source anterior segment optical coherence tomography (SS-ASOCT) in anterior segment diseases. Methods: A systematic literature search was carried out on various medical databases using the keywords, swept source anterior segment optical coherence tomography; SS-ASOCT; Cornea and SS-ASOCT; SS-ASOCT and glaucoma; SS-ASOCT and cataract; SS-ASOCT and biometer; SS-ASOCT and tear film and ocular surface.Original works and novel reports describing the potential role of SS-ASOCT in various anterior segment conditions were included. Results: After a thorough assessment of literature, it was clear that the SS-ASOCT did provide newer insights into many anterior eye conditions. The rapid scan acquisition, deeper tissue penetration, and higher magnification did enhance many of our understandings, which were previously not possible. In addition, lenticular assessment under complex clinical scenarios with automated values on objective scale has made it a worthy tool with immense future possibilities. Conclusions: SS-ASOCT unveiled various anterior segment findings which were of clinical importance.